Policy-Practice Decoupling in Institutionalizing Performance Accountability of Local Government: Case Study of Malang City, Indonesia - Khairul Muluk, Mujibur Rahman; Danar, Oscar Radyan (Local Administration Journal, 2021)
The effective institutionalization of performance management in the public sector is prevented through the process of decoupling. Therefore, this study aims to analyze new regulations on performance agreements and targets for employees in Indonesia’s municipality. This is a qualitative study that was conducted in 2019 on nine local bureaucracies in Malang City using content analysis on performance documents. Furthermore, the data collection was also completed using focus group discussions to confirm the analysis. The results showed that there has been coercive isomorphism, which indicates the existence of institutionalization in local bureaucracies formally pushed by the central government. There is also a decoupling of practices, which showed that political needs have not been achieved. Therefore, more effective institutionalization is needed by providing adequate information and education to all officials and employees involved.